One-Pot Synthesis of Chloropyridines from Aminopyridines via Diazotization; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Lesina Yu. A. Yuliya Aleksandrovna (Materials and Technologies for Biomedical Application and Environmental Engineering, 2016)
Title screen